LA PATAGONIA EN MANUALES Y LIBROS DE LECTURA EL DISCURSO ESCOLAR SOBRE EL “INDÍGENA”: ENTRE LA INVISIBILIDAD Y LA REPARACIÓN HISTÓRICA - Beatriz García, Amelia (Historia Caribe, 2011)
El discurso escolar acerca de la Patagonia -geográfico, histórico y poblacional-que encierran los Manuales y Libros de Lectura usados en escuelasprimarias, han contribuido y contribuyen a la construcción de una representaciónsobre ese espacio del territorio argentino. Particularmenteanalizamos los juegos conceptuales para nombrar al “otro”, al “indio”,asociado al desierto y la “Conquista” con el propósito de indicar continuidadesy rupturas desde mediados del Siglo XX hasta los primeros años dela década del ochenta. Palabras claves Patagonia, Indígena, Conquista, Desierto, Textos escolares. ABSTRACT The books of text, narrowly linked to the pedagogic offers and to the politicalintentions of different projects, a documentation of relevancy is consideredtoday in the study of the History of the regional Education. The schoolspeech brings over of the Patagonia, which they enclose the above mentionedsources, has contributed and contributes to the construction of a representationwith strong effect in the imaginary social one on the Argentine territory. The analysis of the conceptual games to name to “other one”, to the “indio”associated with the desert and the “Conquista”, it allows to indicatecontinuities y/o breaks from the stage territoriana until our days and topay the social debate for the place that they occupy and have occupied theoriginal peoples. The ethnocentric present language in the school texts, hasremained in spite of some “changes”. The recognition of the ethnic andcultural diversity of the country and the way of a new form of joint is forbeing crossed. Key words Patagonia, Indigenous people, Conquest, Desert, School texts.